Eggs Over Evie - Jackson, Alison; Mourning, Tuesday (New York, N.Y. Henry Holt and Company, 2010)
Evie feels unsettled and sad after her parents divorce, her father remarries and takes the family dog, and his new wife becomes pregnant, but a cooking class and helping the elderly lady next door with her cat give Evie a way to cope with the changes in her life. Includes recipes.
Originally published: New York : Henry Holt, c2010
Includes 'GOFISH' questions for the author.
660L
101609
Keywords: Cooking; Divorce; Stepfamilies; Pets; Fiction; Juvenile works